High Abundances of Presolar Grains and 15N-rich Organic Matter in CO3.0 Chondrite Dominion Range 08006 - Nittler, Larry R (Geochimica et cosmochimica acta, 2018)
NanoSIMS C-, N-, and O-isotopic mapping of matrix in CO3.0 chondrite Dominion Range (DOM) 08006 revealed it to have in its matrix the highest abundance of presolar O-rich grains (257 +76/-96 ppm, 2σ) of any meteorite. It also has a matrix abundance of presolar SiC of 35 (+25/-17, 2σ) ppm, similar to that seen across primitive chondrite classes. This provides additional support to bulk isotopic and petrologic evidence that DOM 08006 is the most primitive known CO meteorite. Transmission electron microscopy of five presolar silicate grains revealed one to have a composite mineralogy similar to larger amoeboid olivine aggregates and consistent with equilibrium condensation, two non-stoichiometric amorphous grains and two olivine grains, though one is identified as such solely based on its composition. We also found insoluble organic matter (IOM) to be present primarily as sub-micron inclusions with ranges of C- and N-isotopic anomalies similar to those seen in primitive CR chondrites and interplanetary dust particles. In contrast to other primitive extraterrestrial materials, H isotopic imaging showed normal and homogeneous D/H. Most likely, DOM 08006 and other CO chondrites accreted a similar complement of primitive and isotopically anomalous organic matter to that found in other chondrite classes and IDPs, but the very limited amount of thermal metamorphism experienced by DOM 08006 has caused loss of D-rich organic moieties, while not substantially affecting either the molecular carriers of C and N anomalies or most inorganic phases in the meteorite. One C-rich grain that was highly depleted in 13C and 15N was identified; we propose it originated in the Sun's parental molecular cloud